Historical Records, National Constructions: The Contemporary Popular Music Archive. (1st January 2016) - Baker, Sarah; Doyle, Peter; Homan, Shane
Abstract : This article examines the contemporary role of archives in relation to the curation and preservation of popular music artifacts, drawing upon interviews with a range of archival institutions and popular music curators in several countries. It explores the current technological, financial, and aesthetic challenges facing curators and archivists in the era of digital abundance. Previous strategies of "collecting everything" are being revised, with more recent strategies of selective narratives of particular national significance. This in turn presents further challenges for institutions that wish to adopt more playful and innovative uses of their material, particularly as pressures mount from the state to increase user/visitor numbers. The article also explores how "the national" is configured in these forms and presentations of popular music and cultural memory, and where archives are situated between the music industries, the state, and popular music fan communities.